Analysis of Factors Causing Employee Turnover and How to Retain Talented Employees - Renwarin, Joseph M J (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research aims to determine the effect of ethical climate, social interaction, leadership behavior, and work environment on talent employee retention at Miota International Technology Company. This research uses quantitative methods. Sampling using non-probability sampling saturated. The data collection method used a questionnaire. The sample taken amounted to 136 respondents employees. The data analysis in this research includes validity test, reliability test, classical assumption test, and hypothesis testing. The results of this study indicate that ethical climate has an effect on talent employee retention, social interaction has an effect on talent employee retention, leadership behavior has an effect on talent employee retention, and work environment has an effect on talent employee retention. Ethical climate and social interaction, social interaction and leadership behavior, as well as leadership behavior and work environment simultaneously effect on talent employee retention.